Modern data access with Entity Framework Core : database programming techniques for . NET, . NET Core, UWP, and Xamarin with C# / Holger Schwichtenberg - Schwichtenberg, Holger
"C# developers, here's your opportunity to learn the ins-and-outs of Entity Framework Core, Microsoft's recently redesigned object-relational mapper. Benefit from hands-on learning that will teach you how to tackle frustrating database challenges, such as workarounds to missing features in Entity Framework Core, and learn how to optimize the performance of your applications, head-on!Modern Data Access with Entity Framework Core teaches best practices, guidance, and shortcuts that will significantly reduce the amount of resources you internally dedicate to programming data access code. The proven methods and tools taught in this book, such as how to get better performance, and the ability to select the platform of your choice, will save you valuable time and allow you to create seamless data access. Dive into succinct guidance that covers the gamut-- from installing Entity Framework Core, reverse engineering, forward engineering (including schema migrations), and data reading and modification with LINQ, Dynamic LINQ, SQL, Stored Procedures, and Table Valued Functions- to using third-party products such as LINQPad, Entity Developer, Entity Framework Profiler, EFPlus, and AutoMapper. You'll also appreciate excerpts of conceptual software architecture discussion around Entity Framework Core that might otherwise take years to learn. What You'll LearnUnderstand the core concepts of Entity Framework Core, as well process models for existing databases (reverse engineering) and the generation of database schemas from object models (forward engineering)Study real-world case studies for hands-on EF Core instructionGet up to speed with valuable database access scenarios and code samplesDiscover workarounds to augment missing features in Entity Framework CoreUse Entity Framework Core to write mobile appsBonus online appendix covers Entity Framework Core 2.1 release updatesWho This Book Is ForSoftware developers who have basic experience with .NET and C#, as well as some understanding of relational databases. Knowledge of predecessor technologies such as ADO.NET and the classic ADO.NET Entity Framework is not necessary to learn from this book."